Kinetic of Anthocyanin Degradation in Roselle Extract Dried with Foaming Agent at Different Temperatures - Setia Budi Sasongko; Mohamad Djaeni; Febiani Dwi Utari (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
This research studied the effect of drying temperature on the kinetic of degradation anthocyanin in roselle extract drying with foam under dehumidified air at temperatures ranging 40-60 oC. During the drying process, the anthocyanin content in the roselle extract was observed every 20 minutes for 120 minutes. The data was used for estimating the kinetic parameters of anthocyanin degradation namely constant of anthocyanins degradation rate and reaction order. The kinetic parameters were estimated and fitted with experimental data at various drying condition. Result showed that the anthocyanins degradation closed to the second order reaction. Meanwhile, the constant of anthocyanins degradation rate at various drying temperatures followed Arhenius correlation. With the result, retention of anthocyanin during the drying can be well estimated for various drying time and temperature.